Pediatric kidney transplants with multiple renal arteries show no increased risk of complications compared to single renal artery grafts - Riella, Juliano; Tabbara, Marina M.; Alvarez, Angel; DeFreitas, Marissa J.; Chandar, Jayanthi; Gaynor, Jeffrey J.; González, Javier; Ciancio, Gaetano (Frontiers in Pediatrics, 2022)
Background: Kidney allografts with multiple renal arteries (MRA) are not infrequent and have been historically associated with a higher risk of developing vascular and urologic complications. Reports of kidney transplantation using MRA allografts in the pediatric population remains scarce. The aim of this study was to evaluate if transplantation of allografts with MRA with a surgical intent of creating a single arterial inflow using vascular reconstruction techniques when required, and without the routine use of surgical drains or ureteral stents, is associated with an increased risk of complications when compared to single renal artery (SRA) grafts. Methods: We retrospectively analyzed all pediatric renal transplant recipients performed by a single surgeon at our center between January 2015 and June 2022. Donor and recipient demographics, intraoperative data, and recipient outcomes were included. Recipients were divided into two groups based on SRA vs MRA. Baseline variables were described using frequency distributions for categorical variables and means and standard errors for continuous variables. Comparisons of those distributions between the 2 groups were performed using standard chi-squared and t-tests. Time-to-event distributions were compared using the log-rank test. Results: 49 pediatric transplant recipients were analyzed. Of these, 9 had donors with MRA (Group 1) and 40 had donors with SRA (Group 2). Native kidney and liver mobilization was performed in 44.4% (4/9) of Group 1 vs. 60.0% (24/40) of Group 2 cases (p=0.39). There were no cases of delayed graft function (DGF) or graft primary non-function. No surgical drainage or ureteral stents were used in any of the cases. One patient in Group 2 developed a distal ureter stricture. The geometric mean serum creatinine at 6- and 12-months post-transplant was 0.7 */1.2 and 0.9*/1.2 mg/dl in Group 1 and 0.7*/1.1 and 0.7*/1.1 mg/dl in Group 2. Two death-censored graft failures were observed in Group 2, with no significant difference observed between the two groups (p=0.48). Conclusions: Our study demonstrates that pediatric renal transplantation with MRA grafts, using a surgical approach to achieve a single renal artery ostium, can be safely performed while achieving similar outcomes as SRA grafts and with a low complication rate.